Spatiotemporal pattern analysis of potential light seine fishing areas in the East China sea using VIIRS day/night band imagery. Issue 4 (16th February 2019) - Luo, Lingwei; Kang, Mengjun; Guo, Jinhui; Zhuang, Ying; Liu, Zebin; Wang, Yameng; Zou, Liping
ABSTRACT: Light seine fishing, one of the most efficient methods used in modern fisheries, is performed based on fish phototaxis. In this study, the East China Sea was selected as the study area, and fishing vessel pixels (pixels representing light seine fishing vessels) were detected in five years of Visible Infrared Imaging Radiometer Suite (VIIRS) day/night band (DNB) imagery according to three indicators: the Spike Median Index (SMI), Sharpness Index (SI), and Spike Height Index (SHI). Subsequently, cluster, barycenter, range and direction, and density analyses were conducted to comprehensively evaluate the spatiotemporal patterns of potential light seine fishing areas in the East China Sea. The following conclusions were drawn from the study: (1) the number of fishing vessel pixels exhibited obvious monthly characteristics that are consistent with the fishing moratorium that has been enforced in this region; (2) at the study area scale, light seine fishing occurred in one cluster, and the pattern in the interior of the cluster exhibited spatiotemporal periodicity; (3) the barycenter of the fishing areas displayed opposing movement trends in the first half and the second half of the year, and the movements were closely linked to water temperature changes. In addition, seasonally concentrated fishing areas were observed in winter, spring and summer; (4) the peak fishing month advanced from September to August beginning in 2014, and the fishing areas displayed a strong tendency in orientation that was highly consistent with the distribution of the Kuroshio Front in the East China Sea; and (5) light seine fishing activities were mainly concentrated in the second half of the year, especially in summer, but the intensity has declined in recent years. Our results are in good agreement with the results of other scholars and provide reliable information concerning where and when light seine fishing occurs. These results also suggest that VIIRS DNB imagery can be effectively used to detect light seine fishing areas.